Pertumbuhan Ekonomi Dan Tingkat Pengangguran Di Indonesia Analisis Pengaruh Kunjungan Wisatawan Asing - Rizky Wenaldi Putra; Ali Anis (Universitas Negeri Padang, 2022)
This study aims to identify and analyze; (1) The extent to which the influence of foreign tourist visits on economic growth, (2) The extent to which the influence of investment on economic growth, (3) The extent to which the effect of the exchange rate on economic growth, (4) The extent to which the influence of foreign tourist visits, investment and the exchange rate on growth economy. This research type is descriptive and inductive research. The data used is secondary quarterly time series data from 2010-2020 obtained from related institutions. This study uses a multiple linear regression model with the OLS (Ordinary Least Square) method to find out how the influence of independent variables on related variables. The results of this study indicate that simultaneously, foreign tourist visits, investment and the exchange rate have a significant influence on economic growth in Indonesia. Furthermore, partially (1) foreign tourist visits have a positive and significant effect on economic growth in Indonesia (2) investment has a positive and insignificant effect on economic growth in Indonesia (3) the exchange rate has a negative and significant effect on economic growth in Indonesia. It is further suggested that the government can increase economic growth from various important sectors such as tourism, investment and others.